Multidisciplinary argument for the decriminalization of drugs - Gibson, Sandy (Journal of addictions & offender counseling, 2024)
This manuscript offers an overview of 11 disciplinary perspectives on the failed and destructive War on Drugs and the salutary prospects from decriminalizing drug use, including History, African American studies, Journalism, Sociology, Political Science, Cost Accounting, Urban Education, Counseling, Psychology, Nursing, and Public Health. This offers a roadmap for counselor social and political advocacy with drug policy and highlights community collaboration opportunities.